1980
DOI: 10.1037/0021-843x.89.3.390
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and schizophrenia: An equivalence of cognitive processing.

Abstract: Two tests of creativity were given to 10 paranoid and 10 nonparanoid schizophrenics, 10 nonpsychotic psychiatric controls, and 10 normal subjects. Scores on vocabulary and similarities tests, as well as education, medication, marital status, socioeconomic background, and age, were examined. Results indicated that nonparanoid schizophrenics were significantly more creative than paranoids and psychiatric controls on one creativity measure, a graded level measure of the Alternate Uses Test. Also, nonparanoid schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 24 publications
2
42
0
3
Order By: Relevance
“…As the banal uses are soon exhausted, much of the variation on this task arises from the person's ability to draw possible uses from completely different domains than that for which the object is designed. Schizophrenia patients show a large advantage on this task compared with controls, and indeed, when a group of 'highly creative' normals were tested, their performance was essentially indistinguishable from that of the patients (Keefe and Magaro 1980). A similar pattern is found on a task where non-standard, novel criteria for sorting objects must be devised by the subject (Dykes and McGhie 1976).…”
Section: Imagination and Psychopathologysupporting
confidence: 53%
“…As the banal uses are soon exhausted, much of the variation on this task arises from the person's ability to draw possible uses from completely different domains than that for which the object is designed. Schizophrenia patients show a large advantage on this task compared with controls, and indeed, when a group of 'highly creative' normals were tested, their performance was essentially indistinguishable from that of the patients (Keefe and Magaro 1980). A similar pattern is found on a task where non-standard, novel criteria for sorting objects must be devised by the subject (Dykes and McGhie 1976).…”
Section: Imagination and Psychopathologysupporting
confidence: 53%
“…Eysenck and Furnham, 1993;Gianotti et al, 2001;Kline and Cooper, 1986;Merten and Fischer, 1999;O'Reilly et al, 2001;Poreh et al, 1994;Rawlings and Toogood, 1997;Rushton, 1990;Rust et al, 1989;Graves, 2001, 2002;Woody and Claridge, 1977;Zanes et al, 1998) but currently, there is little support for enhanced creative ability in schizophrenics (Andreasen and Powers, 1975;Cropley and Sikand, 1973;Keefe and Magaro, 1980;Shimkunas and Murray, 1974). Yet, several studies using retrospective analyses of birth records, found support for increased creativity in the relatives of schizophrenic individuals, rather than in the probands themselves (Karlsson, 1970(Karlsson, , 1984.…”
Section: Introductionmentioning
confidence: 99%
“…An individual for whom the involuntary processes operate somewhat less deterministically (but perhaps less efficiently) is more likely to represent environmental data mentally (as well as data recalled from memory) in novel ways. The potential relationship between schizophrenia and creativity (Keefe & Magaro, 1980;Prentky, 1979) would seem to illustrate this factor.…”
Section: A Configural Conception Of Creativitymentioning
confidence: 99%